The effects of digital transformation on corporate energy efficiency: a supply chain spillover perspective - Song, Fangfang (Frontiers in Sustainability, 2025)
IntroductionAs a new enterprise development model, digitalization is an important driver for improving energy efficiency and can provide carbon reduction services across the entire chain.MethodsIn this study, we utilize the panel data of relevant listed firms from 2009 to 2022 to investigate the causal impact of digital transformation on corporate energy efficiency at each node of the supply chain and discuss the moderating effects of digital finance and public environmental concern.ResultsThe empirical results indicate that digital transformation can enhance corporate energy efficiency, and has a forward spillover efficiency-enhancing effect. Further, when a firm adopts digital transformation, it has stronger green innovation and better energy structure leading to higher energy efficiency, and improves the energy efficiency of downstream firms through enhanced green innovation. Moreover, both digital finance and public environmental concern show significant positive moderating effects, and digital finance can positively moderate the contribution of corporate digital transformation to the energy efficiency of downstream firms. Finally, we investigate the heterogeneous treatment impact across different firms, and find that the positive effect is more pronounced in a subsample of state-owned and eastern firms, short-distance downstream firms and downstream firms with low-resource endowments.DiscussionTherefore, a platform should be provided for enterprises to promote digital transformation and unblock the conduction path of green innovation and energy structure in order to realize the green transformation of the entire supply chain.